2017
DOI: 10.1007/s00018-017-2487-z
|View full text |Cite
|
Sign up to set email alerts
|

Microbial carcinogenic toxins and dietary anti-cancer protectants

Abstract: Several toxins are known which account for the ability of some bacteria to initiate or promote carcinogenesis. These ideas are summarised and evidence is discussed for more specific mechanisms involving chymotrypsin and the bacterial chymotryptic enzyme subtilisin. Subtilisin and Bacillus subtilis are present in the gut and environment and both are used commercially in agriculture, livestock rearing and meat processing. The enzymes deplete cells of tumour suppressors such as deleted in colorectal cancer (DCC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 159 publications
(167 reference statements)
1
20
0
1
Order By: Relevance
“…Since chymotrypsin levels in the intestine and circulation are increased with obesity, and since subtilisin is present in processed meat products and agricultural probiotics, it was suggested that these effects might contribute to the associations between a meat-based diet, obesity and carcinogenesis. [11][12][13] The effects of chymotrypsin and subtilisin were prevented by Bowman-Birk inhibitors found in many fruit and vegetables, consistent with the hypothesis that a plant-rich diet would be protective against cancer 11,12 as concluded by several recent epidemiological studies. 14,15 The present work probes further into the interactions between DCC and serine proteases by assessing their effects on markers of Epithelial-Mesenchymal Transition (EMT).…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Since chymotrypsin levels in the intestine and circulation are increased with obesity, and since subtilisin is present in processed meat products and agricultural probiotics, it was suggested that these effects might contribute to the associations between a meat-based diet, obesity and carcinogenesis. [11][12][13] The effects of chymotrypsin and subtilisin were prevented by Bowman-Birk inhibitors found in many fruit and vegetables, consistent with the hypothesis that a plant-rich diet would be protective against cancer 11,12 as concluded by several recent epidemiological studies. 14,15 The present work probes further into the interactions between DCC and serine proteases by assessing their effects on markers of Epithelial-Mesenchymal Transition (EMT).…”
Section: Introductionsupporting
confidence: 81%
“…6 We have recently reported that the cellular expression of DCC, as well as the structurally and functionally related molecule neogenin- [7][8][9] both of which are receptors for the secreted family of netrin proteins 10 can be depleted by the mammalian serine protease chymotrypsin, which is present in the gastro-intestinal tract and systemic circulation, and by the bacterial chymotryptic enzyme subtilisin. 11,12 The removal of DCC and neogenin was accompanied by increased motility and migration in several transformed cell lines including human neuroblastoma (SH-SY5Y) cells and the mammary adenocarcinoma lines MCF-7 and MDA-MB-231. Since chymotrypsin levels in the intestine and circulation are increased with obesity, and since subtilisin is present in processed meat products and agricultural probiotics, it was suggested that these effects might contribute to the associations between a meat-based diet, obesity and carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Contradictory results have also been described when cells were exposed to serine proteases such as mammalian chymotrypsin or the bacterial chymotryptic enzyme subtilisin (27,30). These proteases reduced expression of DCC and neogenin, with changes in the EMT proteins that were not consistent with normal views on their relationship to EMT.…”
Section: Serine Proteases Dgrs and Partial Emtmentioning
confidence: 89%
“…We have shown that DGR function may be regulated by chymotryptic serine proteases which deplete cells of their DGRs, causing increased cell migration (27), actions that may contribute to dietary effects on cancer incidence (28, 29). Subsequently, the effects of this DGR loss on the induction and progression of EMT were considered to identify any relationship between them, as discussed in the following sections in which the major EMT proteins E-cadherin, N-cadherin, β-catenin and vimentin were investigated (Figure 1) (30).…”
Section: Relationships Between Dgrs and Emtmentioning
confidence: 99%
See 1 more Smart Citation